COMPROMETIMENTO ORGANIZACIONAL AFETIVO E ENGAJAMENTO NO TRABALHO COMO PREDITORES DE COMPORTAMENTOS DE CIDADANIA ORGANIZACIONAL - Martins, Vanessa (2014)
Todays organizational environment requires high performance persons and organizations. Organizational citizenship behaviors are considered performance that promote organizational effectiveness and therefore increasingly important to ensure the competitiveness of enterprises. This is a quantitative and transversal study, that aimed to analyze , interpret and discuss the relations of organizational citizenship behaviors, affective organizational commitment and engagement at work, with the last two variables studied as independent variables and predictors in the proposed theoretical model. Participants were 175 employees of different companies in the metropolitan region of São Paulo that responded to an electronic questionnaire containing questions relating to validated scales for the three variables. The collected data were analyzed using the software Statistical Package for Social Sciences, version 19.0 for Windows. Nonparametric statistical analyzes, descriptive analyzes, correlations and hierarchical multiple regression were performed. The results showed that affective organizational commitment demonstrates greater impact on defensive behaviors of the organization; absorption, dimension of engagement at work shown to have a greater impact on the scale of creative suggestions and cooperation with colleagues. The hypotheses were confirmed, and the study led us to conclude that different classes of organizational citizenship behaviors may have different predictors.